Reactive Oxygen Species Accumulation Strongly Allied with Genetic Male Sterility Convertible to Cytoplasmic Male Sterility in Kenaf - Liu, Yiding (Int J Mol Sci, 2021)
Male sterility (MS) plays a key role in the hybrid breed production of plants. Researchers have focused on the association between genetic male sterility (GMS) and cytoplasmic male sterility (CMS) in kenaf. In this study, P9BS (a natural GMS mutant of the kenaf line P9B) and male plants of P9B were used as parents in multiple backcross generations to produce P9SA, a CMS line with stable sterility, to explore the molecular mechanisms of the association between GMS and CMS. The anthers of the maintainer (P9B), GMS (P9BS), and CMS (P9SA) lines were compared through phenotypic, cell morphological, physiological, biochemical observations, and transcriptome analysis. Premature degradation of the tapetum was observed at the mononuclear stage in P9BS and P9SA, which also had lower activity of reactive oxygen species (ROS) scavenging enzymes compared with P9B. Many coexpressed differentially expressed genes were related to ROS balance, including ATP synthase, electron chain transfer, and ROS scavenging processes were upregulated in P9B. CMS plants had a higher ROS accumulation than GMS plants. The MDA content in P9SA was 3.2 times that of P9BS, and therefore, a higher degree of abortion occurred in P9SA, which may indicate that the conversion between CMS and GMS is related to intracellular ROS accumulation. Our study adds new insights into the natural transformation of GMS and CMS in plants in general and kenaf in particular.